Evaluation of Antioxidant, Antidiabetic and Antiobesity Potential of Selected Traditional Medicinal Plants - Sekhon-Loodu, Satvir; Rupasinghe, H. P. Vasantha (Frontiers in Nutrition, 2019)
This study evaluated potential antidiabetic and antiobesity properties in vitro of selected medicinal plants. The hot water (WE) and ethanol extracts (EE) of sweet gale (Myrica gale L.), roseroot (Rhodiola rosea L.), sheep sorrel (Rumex acetosa L.), stinging nettles (Utrica dioica L.) and dandelion (Taraxacum officinale L.) were tested for total antioxidant capacity using ferric reducing antioxidant power (FRAP) and DPPH• scavenging capacity assays, followed by -amylase, -glucosidase and formation of advanced glycation end products (AGE) inhibition assays in vitro. Myrica gale EE had the highest total phenolic content (12.4 mmol GAE/L), FRAP value (17.4 mmol TE/L) and DPPH• scavenging activity (IC50= 3.28 mg/L). Similarly, Myrica gale also exhibited significantly lower IC50 values for the percentage inhibition of -amylase (IC50 =62.65 mg/L) and -glucosidase (IC50 =27.20 mg/L) compared to acarbose (IC50 =91.71 mg/L; IC50 = 89.50 mg/L, respectively) (p ≤ 0.05). The 3T3-L1 preadipocyte study also revealed that Myrica gale EE (54.8%) and stinging nettles (62.2 % EE; 63.2% WE) significantly inhibited the adipogenesis in adipocytes in vitro (p≤ 0.05). Polyphenols present in these medicinal plants have the potential to use in managing type 2 diabetes and obesity.